Pengaruh Stres Akademik Terhadap Kualitas Tidur Pada Mahasiswa Di Jabodetabek - Shofia, Sabrina; Trihandayani, Dewi (Jurnal Ilmiah Penelitian Psikologi, 2023)
Students have the responsibility to complete the tasks they have to achieve the targets to be achieved but are prone to experiencing stress in working on them. This stress is called academic stress. Academic stress is a state of individual in ability that creates negative perceptions when facing academic demands. Students will experience various difficulties such as difficulty concentrating, confused thoughts, easily distracted and difficult to control emotions. Students who experience academic stress tend to have poor sleep quality. This study aims to see whether there is an effect of academic stress on sleep quality among college students in Jabodetabek. This research is a type of quantitative research approach cross sectional with sample technique, purposive sampling. The research sample is 100 students who are in the Jabodetabek area. This research was tested through the IBM SPSS version 26 application system. The data analysis technique used was simple linear regression. The results of completing the questionnaire are disseminated via online (google forms). The research scale used in the research is The Perception of Academic Stress Scale as a measure of academic stress and Pittsburgh Sleep Quality Index as a measure of sleep quality. The results showed that academic stress had a significantly negative effect on sleep quality (R = 0.215 and R2 = 0.046) with probability values of -0.118 which indicates a significant level below 0.05 (P<0.05). So it can be concluded that Ha is accepted, which indicates that there is a significant negative effect of academic stress on sleep quality. Where the higher the academic stress of students, the lower the quality of sleep for students in Jabodetabek. So it is hoped that students can manage their time as an effort to minimize academic stress which can affect sleep quality.